OPTIMALISASI KADAR ABU DALAM PEMBUATAN MINYAK JARAK PAGAR TERVULKANISASI - Santi Puspitasari; Hani Handayani; R. Siti Noviani Melinda; Yoharmus Syamsu (Universitas Nusa Bangsa, 2012)
Optimization of Ash Content on the Synthesize of Vulcanized Jarak Pagar (Jatropha curcas) Oil Developments in the preparation of rubber compound formulations should be followed by a rubber compounder, especially in modifying the formula. Rubber compound composed of rubber as an elastomer and its chemical. Each ingredient has a specific function and influence to the properties of rubber articles. The research studied the formulation of vulcanized oil of Jatropha curcas to obtain the best quality in terms of ash content. The experiment begins with the characterization of Jatropha curcas oil and testing of ash content of each component in the formulation of vulcanized Jatropha curcas oil. The results was used as the basis for formulation of vulcanized Jatropha curcas oil components. Vulcanized Jatropha curcas oil was synthesized at the laboratory scale (100 g oil / batch) at 140OC temperature, agitation speed of 100 rpm, and the variation of dose Na2CO3 and ZnO (0.25; 0.50, and 0.75 pho). Vulcanized Jatropha curcas oil obtained were analyzed for visualization of physical and chemical properties. The experimental results showed that the lowest of ash content of vulcanized Jatropha curcas oil was of 1.24% obtained from the reaction by the addition of 0,25 pho of Na2CO3 and 0,50 pho of ZnO. This dose was defined as the optimal dose because it gived the ash content that meets the requirements of commercial vulcanized oil (max 1.5%).Keywords: Rubber compound, elastomer, Jatropha curcas oil ABSTRAK Perkembangan teknik formulasi dalam penyusunan kompon karet harus dapat diikuti oleh rubber compounder terutama dalam memodifikasi formula tersebut. Kompon karet tersusun atas karet sebagai elastomer dan bahan kimianya. Setiap bahan kimia karet memiliki fungsi dan pengaruh yang spesifik terhadap sifat barang jadi karet. Pada penelitian ini dipelajari formulasi bahan dalam pembuatan minyak tervulkanisasi agar diperoleh mutu terbaik ditinjau dari segi kadar abu. Percobaan diawali dengan karakterisasi minyak jarak pagar dan pengujian kadar abu setiap komponen dalam formulasi minyak jarak pagar tervulkanisasi. Hasilnya digunakan sebagai dasar penyusunan formulasi komponen minyak jarak pagar tervulkanisasi. Minyak jarak pagar tervulkanisasi dibuat pada skala laboratorium (100 g minyak/batch) pada suhu 140oC, kecepatan pengadukan 100 rpm, dan variasi dosis Na2CO3 serta ZnO (0,25; 0,50; dan 0,75 bsm). Minyak jarak pagar yang diperoleh dianalisis visualisasi fisik dan sifat kimianya. Hasil percobaan menunjukkan bahwa kadar abu minyak jarak pagar tervulaknisasi terendah sebesar 1,24% diperoleh dari reaksi dengan penambahan 0,25 bsm Na2CO3 dan 0,50 bsm ZnO. Dosis ini ditetapkan sebagai dosis optimal karena memberikan kadar abu yang memenuhi persyaratan minyak nabati tervulkanisasi komersial (maks 1,5%).Kata kunci: Kompon karet, elastomer, minyak jarak pagar